Vibração de corpo inteiro incidente ao operador de trator agrícola em operação com equipamentos para o preparo periódico do solo - Santos, Viviane Castro dos (2019)
The use of agricultural tractors by operators has caused harmful effects on their health, such as noise and vibration. In addition to adequate working conditions, mechanized operations must be planned with the aim of increasing profitability in the field and reducing costs. For this, it is also necessary that in the design of an agricultural machine are taken into account ergonomic factors, to increase the safety of the machine and improve the quality of work. The objective of the research was to evaluate the exposure of the operator of agricultural machinery to whole body vibrations operating with tractors used in the periodic preparation of the soil. The tractor used was a 4x2 tractor with auxiliary front wheel drive (TDA), brand Valtra®, model BM125i coupled to the following equipment: disc plow, plow of moldboards, off-set grid, rotary hoe and scarifier. For all operations the experimental design was completely randomized. The operations were compared to each other, being five sets (disc-plow, plow-tractor, off-set tractor, rotating tractor, tractor-scarifier) and the tractor without equipment coupled, at two speeds displacement of the tractor (3.5 km.h-1 and 6.1 km.h-1), obtained by the L1 and L3 gears respectively, with engine rotation of 1860 rpm. Finally, the transmissibility (ATEA) was evaluated on each orthogonal axis X, Y and Z for each of the equipment used. The data were processed in Noise Studio® software 6.95. For the statistical treatment of the data the statistical program ASSISTAT version 7.7 beta was used. In order to verify the normality of the data, they were submitted to the Anderson-Darling test. After normality, the data were submitted to analysis of variance by the F test, and when significant, the means were compared by the Tukey test, at 5% significance. The disk plow was equipment that presented greater intensification of the vibrations in all the evaluated parameters. All evaluated sets show statistically equal or higher values in relation to the tractor without attached equipment.